Stability improvement of the grid-tied inverters in the renewable system - Li, Ziqi (2019)
As the unprecedentedly rapid development of technology worldwide, distributed power system (DPS) has been extensively utilized in various industries such as aircraft industry, ship industry, hybrid vehicles industry and medical industry. In a DPS, cascaded configuration plays the role of connecting the subsystems, and it is one of the most representative one of all forms. A representative cascaded system is constituted by a source inverter and a load inverter. However, the issue is that the entire system may become unstable because of the interactions between the source inverter and the load inverter. Previous studies to solve this instability issue can be classified into two main methods which are passive and active methods. Nevertheless, it is rather tough to realize when the stability of the three-phase inverter and a fine dynamic performance need to be guaranteed simultaneously. Hence, this final year project proposed a virtual-impedance-based means to control the load inverter’s input impedance, which could make the three-phase inverter more stable and ensure good dynamic performance at the same time.